2014
DOI: 10.2147/copd.s68226
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific relationships between adverse childhood experiences and chronic obstructive pulmonary disease in five states

Abstract: PurposeAdverse childhood experiences (ACEs) before age 18 have been repeatedly associated with several chronic diseases in adulthood such as depression, heart disease, cancer, diabetes, and stroke. We examined sex-specific relationships between individual ACEs and the number of ACEs with chronic obstructive pulmonary disease (COPD) in the general population.Materials and methodsData from 26,546 women and 19,015 men aged ≥18 years in five states of the 2011 Behavioral Risk Factor Surveillance System were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 27 publications
2
42
4
3
Order By: Relevance
“…Our findings are for the most part consistent with three other studies that examined associations between CM and COPD based on samples from the American population 7,13,14. Using data from 3,000 respondents to the Wisconsin Longitudinal Study, Springer7 found a significant association between CPA and bronchitis/emphysema in adulthood; however, the association did not remain when controlling for mental health and smoking status.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings are for the most part consistent with three other studies that examined associations between CM and COPD based on samples from the American population 7,13,14. Using data from 3,000 respondents to the Wisconsin Longitudinal Study, Springer7 found a significant association between CPA and bronchitis/emphysema in adulthood; however, the association did not remain when controlling for mental health and smoking status.…”
Section: Discussionsupporting
confidence: 90%
“…Many of our findings are similar to those of Cunningham et al14 who examined associations between several childhood adversities, including CPA, CSA, and CEIPV, and COPD using a large sample (n=46,000) of the general population in five American states. Consistent with our results, in the fully adjusted models controlling for sociodemographic variables and smoking status, they found that among females there was a higher likelihood of COPD in adulthood for those who reported CSA and CEIPV, and similar to our findings the association between CPA and COPD did not attain statistical significance.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations